2019
DOI: 10.3390/ijms21010239
|View full text |Cite|
|
Sign up to set email alerts
|

Cell Wall Proteome of Wheat Grain Endosperm and Outer Layers at Two Key Stages of Early Development

Abstract: The cell wall is an important compartment in grain cells that fulfills both structural and functional roles. It has a dynamic structure that is constantly modified during development and in response to biotic and abiotic stresses. Non-structural cell wall proteins (CWPs) are key players in the remodeling of the cell wall during events that punctuate the plant life. Here, a subcellular and quantitative proteomic approach was carried out to identify CWPs possibly involved in changes in cell wall metabolism at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Markers such as AX-94578563 and AX-94941121 associated with DH were present near the gene coding for Invertase/pectin methylesterase inhibitor domain superfamily and sugar-1-phosphate guanyl transferase, respectively. The first has a role in early development of wheat grain endosperm and outer layers (Mehdi et al, 2020 ), which is related to flowering fertilization in flowering plants. Whereas the second one has a role in L-galactose guanyl-transferase, which increases leaf ascorbate content that induces early flowering (Laing et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Markers such as AX-94578563 and AX-94941121 associated with DH were present near the gene coding for Invertase/pectin methylesterase inhibitor domain superfamily and sugar-1-phosphate guanyl transferase, respectively. The first has a role in early development of wheat grain endosperm and outer layers (Mehdi et al, 2020 ), which is related to flowering fertilization in flowering plants. Whereas the second one has a role in L-galactose guanyl-transferase, which increases leaf ascorbate content that induces early flowering (Laing et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this study, we identified seven expansin protein isoforms that significantly accumulated only in the cavity fluid. Expansins could be specifically involved in grain enlargement and seed growth control (Mehdi et al., 2020 ). The functional mechanism of expansin involves disrupting hydrogen bonds between cellulose microfibrils and cross‐linking glycans in the cell wall, permitting turgor‐driven cell wall extension (Mcqueenmason and Cosgrove, 1994 ; Mcqueenmason and Cosgrove, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within this large family, DUF538 superfamily members are among the most studied proteins, found in more than 40 plant species, almost exclusively in Embryophyta [4]. Changes in DUF538 gene expression behavior and protein abundance were observed during different plant developmental and reproductive stages [5][6][7] and in response to various abiotic stresses, including drought [8]; high temperature [9]; carbohydrate deprivation [10]; and nitrogen toxicity [11]. DUF538 protein was also reported to be involved in intracellular transport of cuticular waxes, affecting leaf surface permeability and water loss control [12].…”
Section: Introductionmentioning
confidence: 99%